The incorporation of green peas as the source of dietary fiber in developing functional chicken nuggets - Hana Mohd Zaini; Sylvester Mantihal; Wen, Fiona Yah Ng; Wolyna Pindi (John Wiley & Sons, Inc., 2021)
The effect of green peas (Pisum sativum) on the physicochemical and sensory properties of chicken nuggets was studied. Five formulations were developed in accordance to the incorporation of different percentages of green peas which include control formulations (GPC = 0%, GP3 = 3%, GP6 = 6%, GP9 = 9%, GP12 = 12%). The addition of green peas increases the total dietary fiber (TDF) in the chicken nugget formulation. The incorporation of fiber from green peas altering the physical properties of the sample as an increase in hardness was observed in treated sample with 12% wt/wt green peas (3.243 ± 0.490 N). Based on the sensory scores, there was no significance difference (p < .05) recorded for the attribute of texture. GP9 (9% green peas) was found to be the optimum formulation as it achieved the highest overall acceptance. Green peas are a potential ingredient that can enhance the dietary fiber, improve the texture, and produce appealing sensory properties of chicken nuggets.